Electric power transmission - Osman M.; Abidin I.Z.; Abdullah T.A.R.T.; Marsadek M. (Elsevier Inc., 2023)
Capacitance; Inductance; Converter station; Harmonic filter; HVDC; Line models; Long line; Transmission line models; HVDC power transmission